Observations on the Evolution of the Melanocortin Receptor Gene Family: Distinctive Features of the Melanocortin-2 Receptor - Dores, Robert M. (Frontiers in Neuroscience, 2013)
The melanocortin receptors (MCRs) are a gene family in the rhodopsin class of G protein-coupled receptors. Based on the analysis of several metazoan genome databases it appears that the MCRs are only found in chordates. The presence of five genes in the family (i.e., mc1r, mc2r, mc3r, mc4r, mc5r) in representatives of the tetrapods indicates that the gene family is the result of two genome duplication events and one local gene duplication event during the evolution of the chordates. The MCRs are activated by melanocortin ligands (i.e., ACTH, α-MSH, β-MSH, γ-MSH, δ-MSH) which are all derived from the polypeptide hormone/neuropeptide precursor, POMC, and as a result the functional evolution of the MCRs is intimately associated with the co-evolution of POMC endocrine and neuronal circuits. This review will consider the origin of the MCRs, and discuss the evolutionary relationship between MC2R, MC5R, and MC4R. In addition, this review will analyze the functional evolution of the mc2r gene in light of the co-evolution of the MRAP (Melanocortin-2 Receptor Accessory Protein) gene family.